2023
DOI: 10.3390/healthcare11050633
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Dermatology Care in the Chilean Public Health Sector

Abstract: Due to the Coronavirus-19 (COVID-19) pandemic, most resources of the public health system were allocated to the increasing demand from respiratory patients. From this, it is expected that specialty consultations would decrease drastically. Access to dermatology care in the Chilean public health has been historically limited. To evaluate the impact of the pandemic on dermatology care, the total number of dermatological consultations (DCs) to the Chilean public sector in 2020 is analyzed according to sex and age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…As shown in Figure 3, there is a notable reduction in the teleconsultations evaluated during 2020 as compared to 2019. This is consistent with the overall reduction in consultations to the specialty reported in other settings [36,37] and with the documented reduction of more than 50% of consultations to the specialty observed in the public system in Chile during 2020 [38].…”
Section: Discussionsupporting
confidence: 89%
“…As shown in Figure 3, there is a notable reduction in the teleconsultations evaluated during 2020 as compared to 2019. This is consistent with the overall reduction in consultations to the specialty reported in other settings [36,37] and with the documented reduction of more than 50% of consultations to the specialty observed in the public system in Chile during 2020 [38].…”
Section: Discussionsupporting
confidence: 89%
“…Analogous to Chile experience during 2020, where restrictive measures affected the number of consultations uploaded to the TD system [23][24][25][26], Turkey preference for TD might be reflective of not just its efficacy but also a situational adaptation to the pandemic's challenges. The pandemic, in both settings, would have likely influenced patient mobility and their inclination towards in-person consultations [27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the COVID-19 pandemic and in order to create more capacities for the treatment of COVID-19-positive patients as well as to contain the spread of the virus, the healthcare system was reorganized worldwide as well as in Serbia, leading to decreased access to preventive screening programs such as skin examination and routine dermoscopy. Aragón-Caqueo et al found that the number of consultative dermatology examinations in Chile during 2020 decreased by 52.1% compared to 2019 (from 250,649 in 2019 to 120,095 in 2020) [15]. Tejera-Vaquerizo et al also found that the number of patients in Spain treated for cSCC decreased by 44% during 2020 compared to the number of patients treated during 2019 (770 cases in 2019 and 429 cases in 2020) [40].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has significantly affected hospital admissions for non-COVID-19 patients around the world. While only urgent procedures were performed, all elective and routine diagnostic procedures, as well as routine follow-ups, were postponed and regulated by newly issued protocols [7,[14][15][16][17][18]. O'Conell et al reported a 42,8% reduction in patients admitted for general surgery between 1 March and 30 April 2020 [19,20].…”
Section: Introductionmentioning
confidence: 99%